Evaluation of biocompatibility and toxicity of biodegradable poly (DL-lactic acid) films - Li, Rui-Yun (Am J Transl Res, 2015)
Regeneration and functional recovery of nerves after peripheral nerve injury is the key to peripheral nerve repair. One of the putative therapeutic strategies is to use anti-adhesion polymer films, made of polymeric biomaterials. Recently, a novel biodegradable poly (DL-lactic acid) (PDLLA) film has been prepared using a method of phase transformation with biodegradable polylactic acid polymer as the substrate. This novel, anti-adhesion film has a porous structure, which provides better mechanical properties, better flexibility, more complete diffusion through the polymer of tissue biologic factors like growth factors, and more controllable degradation compared to traditional non-porous films. Little is known, however, about the in vitro and in vivo biocompatibility and cytotoxicity of this type of PDLLA film. Therefore, our aim was to evaluate the biocompatibility and cytotoxicity of this novel PDLLA film using various experimental methods, including a skin irritation test, MTT analysis, and the mouse bone marrow cell micronucleus test, as well as hematology or clinical chemistry measurements in rats after receiving sciatic nerve transection and anastomosis with wrapping of the anastomosis with DLLA films. We demonstrated that exposure to PDLLA film extracts did not generate apparent erythema or edema in rabbit skin and had no effect on the proliferation of Vero cells. Additionally, treatment with PDLLA film extracts did not alter the incidence of micronucleated polychromatic erythrocytes as compared with saline Treated group. Furthermore, implantation of PDLLA film did not alter liver or renal function as measured by serum levels of ALT, AST, TP, A/G, Cr, and BUN, and pathologic examinations showed that implantation of PDLLA film did not cause pathologic changes to the rat liver, kidney, pancreas, or spleen. Taken together, these results suggest that PDLLA films have excellent biocompatibility and no obvious toxicity in vivo, and may be used to prevent nerve adhesion, thereby promoting nerve regeneration.